Demokrasi Pendidikan dalam Perspektif Pendidikan Islam - Nasrulloh, Lalu Nasrulloh; Zulkarnain, Zulkarnain (Al-Riwayah : Jurnal Kependidikan, 2023)
Democracy in Islamic Education is a highly important issue to investigate because it has the potential to provide significant benefits in the development of education, the understanding of democracy, and the understanding of Islamic values in the context of education. The purpose of this research is to identify the principles of democracy in Islamic Education and their implementation in teaching and learning. This research is based on a review of various literature sources that encompass the concepts of democracy in the context of Islamic education, the principles of democracy in Islamic Education, and their implementation in teaching and learning. The research findings reveal (1) the presence of two principles of democracy in Islamic Education: the freedom for educators and learners, where freedom includes the freedom to create, the freedom to develop potential, and the freedom to express opinions. (2) The form of implementing democracy in Islamic education is in the form of idealistic education, which is integral, humanistic, pragmatic, and rooted in strong cultural values. These findings are expected to be of concern to educators in shaping equality in education.